2019
DOI: 10.1155/2019/9141343
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol-Rich Fraction (TRF) Treatment Promotes Proliferation Capacity of Stress-Induced Premature Senescence Myoblasts and Modulates the Renewal of Satellite Cells: Microarray Analysis

Abstract: Human skeletal muscle is a vital organ involved in movement and force generation. It suffers from deterioration in mass, strength, and regenerative capacity in sarcopenia. Skeletal muscle satellite cells are involved in the regeneration process in response to muscle loss. Tocotrienol, an isomer of vitamin E, was reported to have a protective effect on cellular aging. This research is aimed at determining the modulation of tocotrienol-rich fraction (TRF) on the gene expressions of stress-induced premature senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 81 publications
(93 reference statements)
1
14
0
Order By: Relevance
“…They are also transcription factors that assist protein interactions and DNA binding to activate muscle-specific genes [14]. Lim et al found that TRF promoted the proliferation capacity of stress-induced premature senescence myocytes [197]. Moreover, TRF treatment was suggested to modulate the renewal of satellite cells through regulation of p53 signaling, cell cycle, Wnt signaling pathway, and expression of MRF [197].…”
Section: Effects Of Tocotrienol On Muscle Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also transcription factors that assist protein interactions and DNA binding to activate muscle-specific genes [14]. Lim et al found that TRF promoted the proliferation capacity of stress-induced premature senescence myocytes [197]. Moreover, TRF treatment was suggested to modulate the renewal of satellite cells through regulation of p53 signaling, cell cycle, Wnt signaling pathway, and expression of MRF [197].…”
Section: Effects Of Tocotrienol On Muscle Diseasesmentioning
confidence: 99%
“…Lim et al found that TRF promoted the proliferation capacity of stress-induced premature senescence myocytes [197]. Moreover, TRF treatment was suggested to modulate the renewal of satellite cells through regulation of p53 signaling, cell cycle, Wnt signaling pathway, and expression of MRF [197]. It was also shown to reverse senescence in stress-induced pre-senescence myoblasts, demonstrating the potential therapeutic effects of TRF on senescent muscle cells [198].…”
Section: Effects Of Tocotrienol On Muscle Diseasesmentioning
confidence: 99%
“…Sriram et al 47 induced oxidative stress on adipose derived stem cells with H 2 O 2 and showed that Vit-E treatment decreased ROS levels of oxidative stress induced stem cells and significantly increased adipogenesis compared to untreated control. Lim et al 48 showed that Vit-E treatment increased cell proliferation of human skeletal muscle myoblasts through ErbB and FoxO signaling pathways. Vit-E treatment also regulated the renewal of satellite cells (precursor to skeletal muscle cells).…”
Section: Discussionmentioning
confidence: 99%
“…The main trigger for SIPS is oxidative stress. If this stress is experimentally induced in primary myoblast cultures from young subjects, the expression of up to 40 genes becomes modified, predominantly those genes involved in the metabolism of amines, hormonal biosynthesis and activity of lipases [61]. In a relatively recent study carried out on the peripheral muscles of elderly COPD patients with low weight, an increase in proinflammatory factors, oxidative stress and fibrillar damage, as well as regeneration markers, was observed, along with a typical senescent decrease in DNA repair factors, but with no changes in telomere length [62].…”
Section: Premature Senescencementioning
confidence: 99%